ANALISIS KINERJA PEMERINTAH DESA DALAM PEMBANGUNAN INFRASTRUKTUR DI KELURAHAN RENON KECAMATAN DENPASAR SELATAN - I Wayan Wirawan; I Made Winia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2020)
With the enactment of Law Number 32 of 2004 concerning Regional Government, where the implementation of government affairs by the Regional Government and DPRD according to the principle of autonomy and assistance tasks with the principle of broadest autonomy in the system and principles of the Unitary State of the Republic of Indonesia of 1945. The Central Government expects a region it can regulate the needs in the region through regional autonomy, both district / city government affairs and village government affairs so that the resolution of all problems in the region can be quickly resolved by the regional government. In practice, it turns out that Law 32/2004 does not clearly discuss what are the government instruments in the village, so a Government Regulation of the Republic of Indonesia Number 72 of 2005 concerning Villages was drafted again. In principle, this regulation contains several things, among others, which regulates village authority, village government institutions, village apparatus, village planning, and village finance. Performance (performance) is a picture of the level of achievement of the implementation of an activity / program / policy in realizing the goals, objectives, vision and mission of the organization contained in organizational strategic planning.Seeing from the problems and symptoms of the performance mentioned above, the author is interested in examining more deeply by taking the title